Pengaruh Faktor Sarana dan Prasarana terhadap Kinerja Perawat di Ruang Rawat Inap Rumah Sakit Ali Sibroh Malisi Jagakarsa Tahun 2025 - Abdul Hakim; Eka Yoshida; Purwanti Aminingsih (Pusat Riset dan Inovasi Nasional, 2025)
An empirical gap was identified in the initial survey, which revealed rooms with substandard lighting and temperature, and Google reviews indicated that some inpatient nurses performed poorly. The purpose of this study was to identify and analyze the influence of facilities and infrastructure on nurse performance. The research method used a mixed method with a sequential explanatory design, with a sample of 35 inpatient nurses and interviews with hospital management. Quantitative analysis using Chi-Square and Multivariate Logistic Regression and qualitative analysis with inpatient room observation and department interviews. The results of the study were obtained from the variables of lighting, temperature, work support equipment and technological support related to nurse performance (p-value <0.05). Logistic regression analysis showed that the lighting variable was 2.7 times greater (p-value 0.019), temperature 2.9 times greater (p-value 0.054), work support equipment 1.1 times greater (p-vaue 0.032) and technological support 1.5 times greater (p-value 0.040) on good nurse performance compared to poor nurse performance. Conclusion Lighting, temperature, work support equipment, and technological support significantly influence nurse performance, with temperature being the most dominant variable. Suggestions for improving facilities and infrastructure are recommended to further enhance nurse performance.